ANALISIS PROGRAM PEMBERDAYAAN USAHA MIKRO DINAS PERDAGANGAN KOTA SURABAYA DALAM PENINGKATAN EKONOMI - Saifuddin Afif; Sri Umiyati (Policy and Maritime Review, 2022)
Analysis of the Surabaya City Trade Office's Micro Business Empowerment Program in Improving the Economy of Micro Business Actors Case Study on Selendang Semanggi Micro Business, Sambikerep District, Surabaya City in 2019. Etymologically empowerment comes from the basic word "daya" which means strength or ability. Starting from this understanding, empowerment can be interpreted as a process towards being empowered, or a process to gain power, strength, ability, or the process of giving power, strength, ability from those who have power to those who are less or not yet empowered. This study aims to find out how the Micro Business empowerment program run by the Surabaya City Trade Office can improve the economy of Micro Business actors. The theory used is community empowerment which is linked to the Surabaya City RPJMD which has the following programs: Product Standardization Program, Strengthening Business Competitiveness, and Marketing Expansion Program. There are three programs in the Surabaya City RPJMD 2016-2021 which are tools to be able to improve the economy of Micro Business actors.